Diseminasi teknologi diversifikasi olahan produksi tanaman hortikultura di Kabupaten Enrekang - Amal Amal; Uca Uca; Erman Erman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Horticulture and fruit crops such as potatoes, cassava and sweet potatoes are abundant and very much in Enrekang Regency. Diversification of this product is needed to become a product that has economic value by using simple technology and easily absorbed and applied by partners. By that, the objectives in this activity are: (1) the use of simple technology in managing bananas, potatoes and cassava and ginger to be processed with high selling value, (2) increasing community knowledge and skills, (3) stimulating/stimulating the community to utilize and manage into a product that is durable and of high selling value, and (4) increasing income and economy of horticulture farmers. The methods used are (1) Stage desk study, (2) training and demonstration (3) program monitoring and evaluation, (4) reflection on program implementation, and (5) lack of program strengthening and improvement. The output is a simple technology of ginger making into ginger and banana, potatoes and cassava into tasteful and high-economic chips, with packaged ginger and chips ready to be marketed in kiosks. Follow-up is (1) monitoring and evaluating technology dissemination activities that have been carried out in terms of production and marketing, (2) increasing marketing of ginger and chips products to super markets, (3) managing halal labels and testing at POM centers, (4) analyzing household-scale industry of ginger and chips, and (5) developing businesses into home industries that are capable of producing medium-to-medium scale (household scale industries) that are continuous and capable of absorbing labor